Mapping the English Language Needs of Indonesian Hotel Staff: A Systematic Literature Review - Indra Bagus Satrio; Hustarna; Yanto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Indonesia's hospitality industry has grown over the past decade, increasing demand for English proficiency among hotel staff serving international guests. This systematic literature review synthesizes 7 empirical studies conducted across multiple Indonesian regions (Padang, Sikka, Bandung, Kebumen, and Bali) to examine English language needs of hotel employees from 2018 to early 2025. Using Cooper's seven-stage review framework, studies were selected for relevance to front-office roles, empirical rigor, and alignment with Indonesian hospitality contexts. Results indicate front-line staff prioritize speaking and listening for managing check-in and check-out, explaining services, and resolving complaints, while writing supports email correspondence, reservation forms, and guest documentation. Challenges include limited industry-specific vocabulary, difficulty understanding diverse accents, grammatical inaccuracies in complex exchanges, and low confidence. To mitigate these, employees use reactive strategies like translation apps, code-switching to Indonesian, speech simplification, and contextual inference. Proactive measures include scenario-based role-play exercises, digital ESP modules designed for hospitality contexts, and targeted vocabulary workshops. By systematically consolidating previously fragmented research, this review identifies consistent patterns across geographic contexts and workplace settings, revealing a significant gap between general English instruction and the specialized communicative demands of hotel work. Findings advocate for ESP curricula that integrate authentic hotel materials, simulated guest interactions, and focused vocabulary development. These insights inform educators, ESP curriculum developers, hotel managers, and human resource professionals aiming to enhance service quality and guest satisfaction in Indonesia's tourism sector.